KEBEBASAN BERAGAMA PERSPEKTIF HAK ASASI MANUSIA - I WAYAN PUSPA; I MADE SURADANA; SYAIFULLAH SYAIFULLAH; TRI LAKSONO KURNIAWAN; MUHAMMAD IKBAL (GANEC SWARA, 2023)
Violations of freedom of religion and worship often occur among the community. If this is allowed to happen, it is feared that it could lead to divisions that lead to the disintegration of the nation. The problem is: "How is the guarantee of freedom of religion and worship in international human rights instruments and in national human rights instruments?" This research is normative legal research, by examining legal materials, both primary legal materials, secondary legal materials and tertiary legal materials. Analysis of legal materials was carried out qualitatively. The research results show that guarantees of religious freedom have been explicitly regulated in both international human rights instruments and national human rights instruments. International human rights instruments are regulated in Article 2 of the General Declaration of Human Rights, and Article 18 of the International Covenant on Civil and Political Rights (ICCPR). Meanwhile, the National Human Rights instrument is guaranteed in the 1945 Constitution of the Republic of Indonesia, namely in Article 28E paragraphs (1) and (2), and Article 29 paragraph 2); Article 22 of Law Number 39 of 1999 concerning Human Rights, and Law Number 12 of 2005 concerning Ratification or Ratification of the International Covenant on Civil and Political Rights (ICCPR), namely in Articles 2 and Article 18. States are expected to be able to implement the provisions in both international human rights instruments and national human rights instruments in providing guarantees of freedom for every person to embrace their own religion and to worship according to that religion and belief